Mapping of Performance Measurement Models in Public Sector Organizations: a Hybrid Review - Nuwun Priyono; Puji Harto (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2026)
This study aims to map the various performance measurement models currently in use and their contribution to improving the performance of public sector organizations. This study uses a hybrid review method that combines bibliometric and literature review approaches. The bibliometric review uses Vosviewer visualization and citation counts. The Systematic Literature Review (SLR) uses the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) method, with an observation period from 2005 to 2025. This research focuses on a long-term period, enabling it to capture longitudinal trends in the development of performance measurement models. This research not only maps the models but also identifies the dominant models and analyzes their contribution to improving organizational performance. Using Publish or Perish, 200 articles were obtained from Scopus; however, only 26 articles included the compiled terms. The results of the hybrid review research show that, of the 26 articles, 18 map various performance measurement models. The most widely used model is the study named Balanced Scorecard (BSC). Some other models include the concept of value for money, the Public Sector Scorecard (PSS), and the balanced stakeholder model. The articles that met these criteria included one with the highest number of citations (94) and two with no citations. Then, 26 articles explain how various measurement models contribute to improved performance in public-sector organizations. Performance measurement models have been proven to contribute to improving the effectiveness and efficiency of public sector organizations, supporting performance-based decision-making and enhancing public accountability. This study integrates the principles of bibliometric and structured reviews to map performance measurement models and their contributions to improving the performance of public sector organizations. Theoretical implications: enrich the literature on performance measurement models through an integrative approach and demonstrate that no single model is superior. Strengthens the Balanced Scorecard's position as the dominant model, while still allowing for the development of alternative models. Practical implications: provide guidance for organizations on selecting and adapting performance measurement models that suit their needs and encourage a multi-model approach.